ACSM's resources for the group exercise instructor - DeSimone, Grace (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"ACSM's Resources for the Group Exercise Instructor gives you the knowledge and the skills you need to effectively lead group exercise. You'll learn how to take advantage of group dynamics to improve health and well-being. You'll also discover how to work with clients with special needs, so that everyone can safely benefit from group exercise. Moreover, the book shows how the skills you'll gain can easily be adapted to different environments, including gyms, studios, recreational facilities, and clubs. Developed by the American College of Sports Medicine (ACSM), this book thoroughly prepares you to become an ACSM Certified Group Exercise Instructor. Following an introduction, which includes a profile of a group exercise instructor, the book covers such topics as leadership, class design, legal issues and responsibilities, and exercise science. The book's accompanying video demonstrates how the techniques discussed in the book are put into practice during an actual group exercise class"--Provided by publisher.